Evaluation of the color measurement based on a microscopic hyperspectral imaging system. Issue 6 (28th April 2021) - Qiu, Kebin; Chen, Weiguo; Zhou, Hua; Wang, Chenglong; Cui, Zhihua
Abstract: In order to make a color assessment for micron‐grade materials such as a single fiber, a non‐destructive and push‐broom microscopic hyperspectral imaging system (MHIS) was set up consisting of a stereomicroscope, an imaging spectrograph, and a digital detector. The performance of this system for acquiring accurate and repeatable information, such as spectral and colorimetric values, was investigated. The experimental results show that the system has an excellent spatial resolution, repeatability, and accuracy. The spatial resolution with a ×1.5 auxiliary objective lens was down to 90.244 lp mm −1 (5.54 μm). The average Δ E 00 of the tested patches in the ColorChecker Mini chart was between 0.15 and 0.40, and the color measurement repeatability was acceptable. Color difference Δ E 00 and the standard variation of spectral wavelength between ×2.5 and ×4.5 magnification were larger than those at lower magnifications. It can be concluded that the MHIS can identify colorimetric values of the materials and detect the color changes sensitively with a high spatial resolution at micron‐grade.